Respostas
respondido por:
0
( z³ * z⁻⁴ )/ ( z⁻⁶ * z⁸ * z²)
NUMERADOR
( Z )³⁻⁴ = Z⁻¹ ( CONSERVA A BASE SOMA OS EXPOENTES)
DENOMINADOR
( Z )⁻⁶⁺⁸⁺² = Z⁴ ( IDEM ACIMA)
REESCREVENDO
( Z ) ⁻¹ / ( Z )⁴ ( DIMINUI OS EXPOENTES )
( Z )⁻¹⁻⁽⁺⁴⁾ = ( Z ) ⁻¹⁻⁴ = ( Z )⁻⁵ ****
NUMERADOR
( Z )³⁻⁴ = Z⁻¹ ( CONSERVA A BASE SOMA OS EXPOENTES)
DENOMINADOR
( Z )⁻⁶⁺⁸⁺² = Z⁴ ( IDEM ACIMA)
REESCREVENDO
( Z ) ⁻¹ / ( Z )⁴ ( DIMINUI OS EXPOENTES )
( Z )⁻¹⁻⁽⁺⁴⁾ = ( Z ) ⁻¹⁻⁴ = ( Z )⁻⁵ ****
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás